Applications of Photodynamic Therapy in Management of Periodontal Disease - A Review - Inasu, Shiny; Thomas, Biju (Journal of Health and Allied Sciences NU, 2018)
A novel noninvasive photochemical approach for infection control, namely photodynamic therapy, has received much attention in the treatment of oral diseases which requires three nontoxic ingredients namely visible harmless light, a photosensitizer and oxygen are involved in this therapy. It is based on the principle that a photosensitizer binds to the target cells which when activated by light of a suitable wavelength results in the production of singlet oxygen and other very reactive agents that are extremely toxic to certain cells and bacteria. This article highlights the application of photo-dynamic therapy in management of periodontal disease and its current status.
Keywords: photo-sensitizer; visible light; oxygen; periodontitis; applications